Sirolimus as an alternative treatment in patients with granulomatous‐lymphocytic lung disease and humoral immunodeficiency with impaired regulatory T cells. Issue 4 (17th April 2018) - Deyà‐Martínez, Angela; Esteve‐Solé, Ana; Vélez‐Tirado, Natalia; Celis, Veronica; Costa, Jordi; Cols, Maria; Jou, Cristina; Vlagea, Alexandru; Plaza‐Martin, Ana María; Juan, Manel; Alsina, Laia
Abstract: Background: One of the most frequent non‐infectious complications of humoral immunodeficiencies with a CVID‐like pattern is a particular form of inflammatory lung disease which is called granulomatous‐lymphocytic interstitial lung disease (GLILD). Its development worsens patient prognosis, with a significant decrease in survival. Currently, there are no unified guidelines regarding its management, and different combinations of immunosuppressants have been used with variable success. Methods: Clinical and radiological data were collected from patient's medical charts. Flow cytometry was performed to characterize the immunological features with special focus in regulatory T cells (Tregs). Results: A 16‐year‐old girl with Kabuki syndrome and a 12‐year‐old boy, both with a CVID‐like humoral immunodeficiency on immunoglobulin replacement treatment, developed during follow‐up an inflammatory complication radiologically, clinically, and histologically compatible with GLILD. They required treatment, and sirolimus was started, with very good response and no serious side effects. Conclusions: These 2 cases provide insight into the underlying local and systemic immune anomalies involved in the development of GLILD, including the possible role of Tregs. Combined chemotherapy is commonly used as treatment for GLILD when steroids fail, but there have been some reports of successful monotherapy. As far as we know, these are the first 2 GLILD patients treated successfully with sirolimus, suggesting the advisability of further study of mTOR inhibitors as a more targeted treatment for GLILD, if impairment in Tregs is demonstrated.